Evaluation of a digital application to support internationally qualified nurses' communication and leadership skills. (September 2021) - Aggar, Christina; Shinners, Lucy; Penman, Olivia; Mainey, Lydia; Kurup, Chanchal; Hallett, Jane; Doran, Frances; Raddi, Sudha
Abstract: Background: Internationally qualified nurses enrolled in Australian bridging programs to support professional registration lack confidence, and require support and time to develop communication and leadership skills in the clinical setting. Strategies that strengthen professional self-concept have been demonstrated to improve the nursing performance of internationally qualified nurses. Objective: To evaluate an interactive mobile application called m Preceptor, specifically designed to support internationally qualified nurses' communication and leadership skills during a 6 week clinical placement. The application facilitated weekly learning content and activities in the areas of clinical communication and leadership, including self-assessment, goal-setting, case studies, and weekly detailed reflections while on placement. Design: A quasi-experimental pre and post-test design with a non-equivalent comparison group was used to explore the effectiveness of m Preceptor on internationally qualified nurses' self-appraisal of professional self-concept, including leadership and communication skills, compared with standard clinical placement. The psychometrically tested Nurse Self-Concept Questionnaire, measured changes to perceived professional self-concept. Results: Overall, there was a significant increase in Nurse Self-Concept following the clinical placement, confirming that the bridging program for internationally qualified nurses in Australia improves leadership and communication skills. Leadership skills were significantly greater for those internationally qualified nurses who engaged with m Preceptor. Conclusion: Further research is required to investigate the application of interactive mobile applications, as effective education resources to facilitate internationally qualified nurses' transition of skills and knowledge to the Australian healthcare context. Highlights: Bridging programs support international nurses' professional self-concept. Mobile applications are effective resources to support nurses' leadership skills. More research required exploring the efficacy of mobile education to support nurses.